Functional health literacy in a group of Turkish patients: A pilot study - Bilgel, Nazan (Cogent social sciences, 2017)
Background: There is currently no objective original measure developed in the Turkish language for evaluating health literacy. However, some instruments originally developed in Western countries and translated into Turkish do exist. Aims: The aim of this study was to translate and adapt the Test of Functional Health Literacy (TOFHLA) into the Turkish language and validate it among a group of Turkish patients. Methods: Interviews were held in an outpatient clinic. Illiterate patients, those with previously diagnosed mental illness and inadequate visual acuity were excluded. Results: Internal consistencies of the reading comprehension and numeracy items were 0.89 and 0.77, respectively. Inadequate health literacy was determined in 28.0% of participants, marginal in 30.0%, and adequate in 42.0%. Among the possible socio-demographic predictors of health literacy, the most significant predictor was the educational level. Participants with lower levels of education had significantly lower levels of health literacy. In general, reading comprehension scores were lower than the numeracy scores. The most disadvantaged groups were women and older people (≥40 years of age) because of their lower levels of education. Discussion: The TOFHLA in the Turkish language seems to be a valid measure. Functional health literacy was found to be inadequate or marginal. Without enhancing the overall educational level, especially of women, efforts to improve health literacy seem to be ineffective. Conclusions: Functional health literacy is related to education. Non-written visual materials should be considered as a temporary solution to improve health literacy in populations with low literacy.